'I don't engage': Online communication and social media use among New Zealand journalists. (April 2018) - Neilson, Tai
Social media, comment threads, and other means of online communication are important to journalists' work processes, but expand their workload and pose challenges to their professional identity. The concept of 'engagement' is used by news workers in New Zealand to describe the role of digitally mediated communication in their work. Engagement deserves scholarly treatment akin to concepts such as 'participatory journalism' because it is employed by journalists to place professional and practical limits on online interaction. Their decisions about engagement are based on professional commitments, past experiences, and the allocation of time and resources. Journalists in newsrooms that are already understaffed and under-resourced are expected to take on new tasks; like other digital laborers, journalists experience the interpenetration of work and leisure and the incorporation of affective and unpaid work. News workers have an opportunity to develop best practices for engagement and determine how and when they should engage online.